Critical Synthesis Package: Health Professional's Attitude Towards the Homeless Inventory (HPATHI) - Sheila M. Crow (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Health Professional's Attitude Towards the Homeless Inventory (HPATHI), and (2) a copy of the HPATHI instrument developed by David Buck, MD. The HPATHI is a short, self-administered instrument with 19 items, divided into subscales titled: Personal Advocacy, Social Advocacy, and Cynicism. Personal Advocacy measures a personal commitment to work with the homeless, and Social Advocacy assesses attitudes regarding society's responsibility to care for the homeless population. Cynicism measures a negative attitude and sense of futility in working with the homeless. The response options are presented along a 5-point Likert scale for each item. Higher scores indicate more favorable attitudes towards homelessness. The HPATHI has been demonstrated to respond to change in the attitudes about homelessness in medical students, residents, and practicing physicians. The scale also demonstrates concurrent validity with one other instrument used to gauge attitudes towards the homeless. Studies designed to validate the instrument with students and faculty across health professions and across specialties within medicine are needed.